Analysis and forecast of ensuring the reliability of the Kyrgyz energy system in the draft of "Concept for the development of energy in the long-term perspective - Kasymova Valentina; Arkhangelskaya Anna; Kurzhumbaeva Roza (E3S Web of Conferences, 2017)
In this article, based on the work done to prepare the project of the Concept of development of the fuel and energy complex of the Kyrgyz Republic until 2030 identifies the main directions for the development of the country's energy sector in the medium-term perspective, including ensuring sustainable and uninterrupted electricity and fuel supply for the development of the economy and population needs, the introduction of new technologies using renewable energy sources, institutional reforms, financial recovery of energy companies, etc. In addition, the main priorities of the state energy policy, priority tasks and policy measures on scenarios are outlined.